Inovasi Pembelajaran Pendidikan Kewarganegaraan: Pengembangan Media Pembelajaran Google Sites dan Aplikasi Android Untuk Mahasiswa - Al Fikri, Muhammad Arif (Jurnal Kewarganegaraan, 2025)
The purpose of the study was to develop Google Sites and Android applications and to find out the responses of FTIK UIN Salatiga students in learning Citizenship. The development research used the ADDIE model through 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at FTIK UIN Salatiga. Development through the analysis stage consists of needs analysis and material scope. The design stage involves making flowcharts and storyboards. The development stage is collecting materials and producing Google sites and Android applications called "Belajar PKn." The Implementation stage was carried out in 3 classes with 73 students who filled out the media response questionnaire. Finally, student evaluation of the media. The results of this study developed Google Sites and Android applications, which are innovations in citizenship learning. The evaluation carried out by users, namely 73 students, got an average of 78.7 (feasible category), while the PKn lecturer got an average of 86.3 (very feasible category). So, it can be concluded that Google Sites and Android applications can be used more widely for citizenship courses. Its novelty combines both types of media, Google sites, and Android applications, while many studies have only developed one of the media. Suggestions for further research are to add interactive features to increase student involvement.